Attempt of integration of a small commercial ammonia-water absorption refrigerator with a solar concentrator: experience and results - Busso, A. (2011)
The integration of a small commercial ammonia-water absorption refrigerator with a solar concentrator as heat source was analyzed theoretically and experimentally. Operation parameters of the fridge were determined by parametric fitting experimental data using a thermodynamic model of the cycle leading to a working pressure of 25 bar, weak and strong solution concentrations of 15% and 30% respectively and a COP of ∼0.18. As sold, the fridge can operate with a reduction in the electric power supply of up to 40%. Results showed that the Parabolic Concentrator (PC) used can deliver temperatures above 200 °C for almost 6 h with an average useful power delivery and efficiency of 530 W and 26% respectively. During laboratory test runs it was possible to hold the refrigeration cycle running in a very unstable regime despite the inappropriate heat distribution in the generator unit due to the lower temperature heat source used (220 °C). However, outdoor testing with the sun as energy source proved unsuccessful due to the higher heat losses that occur at the pipes connecting the PC with the fridge.